Dual-Polarized Reflectarray for High-Speed Satellite Communication - Yilmaz, Selda; Gulseren, Ahmet Hulusi; Tokan, Nurhan Turker (IEEE, 2023)
In this paper, a reflectarray consisting of a novel unit cell is proposed. The dual polarized unit cell consists of a cross dipole and 4 L-shaped dipoles. Phase delay diagram is obtained and by the quantization process, physical dimensions are established to radiate to a specific direction, namely to theta = 20 degrees Ka-band downlink frequency. An efficiency analysis is carried out to determine f/D ratio. The reflectarrray is simulated in CST Microwave studio. The simulation results show that the reflectarray consisting of the proposed novel unit cell works efficiently in both TE and TM modes.
Keywords: reflectarray; unit cell; dual polarization; DESIGN; Engineering; Remote Sensing